2020
DOI: 10.1186/s12882-020-01745-5
|View full text |Cite
|
Sign up to set email alerts
|

The association of kidney function and cognitive decline in older patients at risk of cardiovascular disease: a longitudinal data analysis

Abstract: Background: Chronic kidney disease (CKD) has been identified as a significant direct marker for cognitive decline, but controversy exists regarding the magnitude of the association of kidney function with cognitive decline across the different CKD stages. Therefore, the aim of this study was to investigate the association of kidney function with cognitive decline in older patients at high risk of cardiovascular disease, using data from the PROspective Study of Pravastatin in the Elderly at Risk (PROSPER). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…An alternative explanation might be a false positive finding due to multiple comparisons. Evidence of a potential association between severe kidney impairment and cognitive decline was presented in a recent longitudinal review study (n = 5796) by Zijlstra et al [50]. The authors found that in older individuals with vascular burden, only severe kidney dysfunction, correspondent to eGFR < 30 ml/min/1,73 m 2 [7,8], was associated with cognitive decline over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation might be a false positive finding due to multiple comparisons. Evidence of a potential association between severe kidney impairment and cognitive decline was presented in a recent longitudinal review study (n = 5796) by Zijlstra et al [50]. The authors found that in older individuals with vascular burden, only severe kidney dysfunction, correspondent to eGFR < 30 ml/min/1,73 m 2 [7,8], was associated with cognitive decline over time.…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of this longitudinal study is the large number of participants recruited, representing a general population of the (younger) elder population. Another strength is the long follow up time of 6 years, which can be compared to the mean follow up time of 3.2 years, in the review study of Zijlstra et al [50] mentioned above. Yet another strength is the wide panel of cognitive tests used, covering most of the cognitive domains, and also the small test administrator effects on cognitive performance, since only 1.4-3.5 % of the total variation in test scores was explained by the factor attributed to the test administrator [57].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment is a well-recognized complication of CKD [ 18 ]. Evidence from the literature found a worsening of cognitive function as the kidney function declines [ 44 , 45 , 46 ]. A recent cohort study using clinical practice research datalink found a co-occurrence of CKD and dementia in the real-world setting [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment is increasingly prevalent in aging and multi-morbid populations. Chronic kidney disease (CKD) is also increasing in prevalence and after correcting for shared vascular risk factors within an aging multi-morbid population, advanced CKD is independently associated with cognitive impairment ( 1 ). Kidney replacement therapies (KRT) with dialysis or kidney transplantation carry a cognitive burden in themselves, from the lifestyle demands and healthcare interactions demands on patients through to marked physiological stressors and unique cardiovascular instability.…”
Section: Introductionmentioning
confidence: 99%